Reflections on teaching the humanities at university - Fuentes Mejía, Cristina (Universidad Pedagógica y Tecnológica de Colombia, 2013)
Abstract This paper presents the reflection on the sense of Humanities teaching and learning process at XXI century university. The reflection starts from the innovative experience of Museo Comunitario (Community Museum) as a strategy of intervention and research, implemented in a private university in Tunja City. First of all, it is presented an introduction that puts the reader into the context of questioning the Humanities and their crisis from the educative field. In the second part of the paper, the self-referential exercise of the Humanities teaching in higher education is gathered. Later, the text focuses on the uprising of the crisis of the Humanities and how it must be recognized from the educative field. Right after, it is showed, as a way of systematizing the experience, the Museo Comunitario as a didactic strategy that enables a social constructive environment going beyond the walls of the classroom. The text ends with some results and conclusions of the reflection in general and of the implementation of the didactic strategy.